Prosthetic rehabilitation for a patient with systemic sclerosis and sjögren's syndrome: a clinical report and review. (2nd May 2019) - Oluwajana, Funmi; Ferguson, Lucy; Wragg, Phillip
Abstract : Systemic sclerosis, although a rare disease, has numerous direct and indirect effects on the oral cavity. This article aims to inform clinicians of the signs and symptoms they may see in patients with the disease and the impact it can have on dental management. The main effect, microstomia, is not just limited to systemic sclerosis, thus the clinical and laboratory techniques described may be helpful when managing other patients with limited mouth opening. CPD/Clinical Relevance: Clinicians should be able to recognize how systemic sclerosis will have an impact on their patient's oral health and implement management plans to prevent deterioration of their dentition. The novel techniques used will provide dentists and dental technicians with alternative techniques that can be employed in a variety of cases when considering prosthetic rehabilitation.